Komunikasi Pemasaran Digital sebagai Strategi Mahasiswa KKN untuk Pemberdayaan UMKM Keripik Jahe di Desa Karang Anyer, Kabupaten Simalungun - Mailin Mailin; Nanda Ardi Tama; Nadhilah Nazlah Nst; Anisah Harahap; Ahyarul Juanda Sagala (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2026)
This study aims to describe the role of Community Service Program (KKN) students in implementing digital marketing communication as a strategy to empower ginger chips micro, small, and medium enterprises (MSMEs) in Karang Anyer Village, Simalungun Regency. The background of this research is the low utilization of digital communication technology in promoting local products, which has resulted in MSMEs relying mainly on traditional marketing practices. This research employed a descriptive qualitative method with data collected through observation, in-depth interviews with MSME actors and KKN students, and documentation.The findings reveal that KKN students act as facilitators, companions, and innovators in introducing digital marketing communication strategies through the use of social media, online marketplaces, and locally based promotional content. Their role has contributed to improving digital communication skills, expanding market reach, and strengthening the brand image of ginger chips as a competitive local product.In conclusion, the involvement of KKN students not only provides practical contributions to the development of ginger chips MSMEs but also strengthens the community’s digital communication capacity in a sustainable manner.